Service Selection Based on a Practical Interface Assessment Scheme [Thomson ISI, IF JCR2013=1.579] - Garriga, Martín (2013)
Service-Oriented Computing promotes building applications by consuming reusable services. However, facing the selection of adequate services for a specific application still is a major challenge. Even with a reduced set of candidate services, the effort of assessing candidates could be overwhelming. We have defined an approach to assist developers in the selection of services, which mainly comprises an assessment process for service Interface Compatibility. This assessment process is based on a comprehensive structural scheme for services' interfaces matching. The scheme allows developers to gain knowledge on likely services' interactions and their required adaptations to achieve a successful integration. We evaluated the performance of the Interface Compatibility analysis with a data-set of 453 services and two different service discovery registries. The experiments shown an improvement of up to 17% in precision and up to 8% in the DCG usefulness metric, with regard to the previous results obtained using only textual (syntactical) queries.